Ensilability characteristics of chia (Salvia hispanica L.) during its growth cycle and fermentation pattern of its silages affected by wilting degrees - Peiretti, P. G. (Cuban Journal of Agricultural Science, 2010)
The chia was grown in the Po valley, northern Italy. The chia growth was characterised by a rapid dry matter (DM) accumulation in the herbage during development and the DM content increased from 84 to 224 g/kg fresh matter (FM). Significant differences were observed in the pH, that range from 6.0 to 6.2. The water soluble carbohydrates (WSC) content increased from 86 to 213 g/kg DM, while the buffering capacity (BC) decreased from 689 to 416 meq/kg DM with increasing growth stage. The soluble nitrogen (SN) ranged from 105 to 174 g/kg TN. Four types of silage were prepared with no additives (cut silage and wilted silages at three levels of wilting) at budding stage to investigate the effects of wilting on the chemical composition and fermentation characteristics of the silage. The results of ensiling indicate that the fermentation of chia is characterized by the presence of some alcohols and volatile fatty acids and a lack of lactic acid. The variability in the herbage quality characteristics harvested at five different stages of maturity and the variability in the silage characteristics were analysed for their statistical significance via analysis of variance (ANOVA) to test the effect of the growth stage and wilting level, respectively. No significant differences were found in TN, gross energy, pH or the fermentation characteristics, with the exception of isobutyric acid, which decreased with increasing wilting level. The good results obtained in lab-scale silos, with silage characterised by a restricted fermentation and a lack of butyric acid at the three high wilting levels, would seem to suggest that chia has the potential for large scale ensiling, if it is harvested at budding stage and wilted to a DM level of more than 285 g/kg FM. Further research is required to define the conservation quality in farm scale silos or in lab silos with additives that improve silage fermentation when chia is ensiled at cut or at low wilting levels. Key words: chemical composition, water soluble carbohydrates, conservation quality, silage